Análise de eficiências de máquinas industriais por meio de um modelo multiobjetivo de análise envoltória de dados combinada com o Overall Equipment Effectiveness - Peres Gonçalez, Augusto Araujo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Since the implementation of the Toyota Production System, the industries seek to embrace the lean production, aiming for the increase of speed and productivity on their production lines. For its proper implementation, indicators are required to present the equipments status and to monitor its evolution, being the Overall Equipment Effectiveness (OEE) the main indicator applied. However, the commonly used methods may not be those which represents reality with the most accuracy. This paper intends to apply the BiO-MCDEA model and the OEE together in order to avaluate the efficiency of machines located in a company of the industrial sector in the Paraiba Valley, creating a ranking of the most efficient machines with each method alone and then with both together. It is shown that the DEA BCC model could not be applied, requiring the use of the BiO-MCDEA model, due to its more critical analysis. With the combination of both indexes, the Global Efficiency Index was obtained, providing input and output goals in order to transform inefficient DMUs into efficient ones

Desde o surgimento do Sistema Toyota de Produção (STP), as indústrias visam adotar um sistema de produção enxuta, que busca o aumento da velocidade e produtividade de suas linhas. Para a correta implementação desse sistema, são necessários indicadores que demonstrem a situação das máquinas e acompanhem sua evolução, sendo o Overall Equipment Effectiveness (OEE) o principal indicador aplicado. Entretanto, os métodos comumente utilizados podem não ser os que melhor representam a realidade com maior precisão. Esse trabalho visou a utilização do modelo bi-objective Multi-Criteira BiO-MCDEA em conjunto com o OEE para a avaliação da eficiência de máquinas de uma empresa do setor industrial hidraúlico do Vale do Paraíba. Com a junção de ambos os índices foi então obtido o chamado de Índice Global de Eficiência, proporcionando metas de inputs e output a fim de transformar as DMUs ineficientes em eficientes
Keywords: Produção enxuta; Pesquisa operacional; Máquinas - Indústria; Lean manufacturing